The clinical efficacy of a mixture of ivy leaf extract and coptidis rhizome in patients with idiopathic pulmonary fibrosis. Issue 5 (3rd February 2023) - Lee, Jae Ha; Jang, Ji Hoon; Park, Jin Han; Jung, So Young; Lee, Sunggun; Kim, Seong-Ho; Kim, Ji Yeon; Ko, Junghae; Choi, Hee Eun; No, Tae-Hoon; Jang, Hang-Jea
Abstract : Idiopathic pulmonary fibrosis (IPF) is a progressive fibrotic lung disease with poor prognosis and cough is the one of most common and major symptoms in IPF. The aim of this study was to evaluate the clinical efficacy of a Mixture of Ivy Leaf Extract and Coptidis rhizome (Synatura®) in patients with IPF. This was a prospective, open-label, single-center, and single-arm study in Korea from October 2019 to September 2020. IPF patients with chronic bronchitis were enrolled. Between baseline and eight weeks after use of Synatura®, clinical measures regarding cough and health-related quality of life, and the systemic inflammatory markers was prospectively collected. Thirty patients were enrolled. Median age was 73 years and 86.7% were men. The median gender-age-pulmonary function stage of IPF was 3. Baseline total score of Leicester cough questionnaire (LCQ) and St. George respiratory questionnaire (SGRQ) were 104.5 and 30.59 respectively. After eight weeks, there was no significant improvement in LCQ (16.8 [15.6–19.1] vs 17.5 [15.2–18.9], P = .772) and SGRQ (30.6 [19.4–37.8] vs 29.9 [19.6–41.8], P = .194) scores. Also, there was no significant difference of systemic inflammatory markers. In analysis of minimal clinically important differences (MCID), one third (33.3%) patients fulfilled the criteria of MCID (1.3) in LCQ scores and median differences was 14 (range: 10–18). In terms of SGRQ, 6 patients (20%) reached MCID (4.0) without significant predictive factors. In our study, use of Synatura® during 8 weeks improved cough-specific life quality in one third patients with IPF. Large-scale, randomized, double-blind, and placebo-controlled clinical trials are needed.